Implementasi Sistem Akuntansi Pembiayaan Murabahah pada Bank Syariah Mandiri KC Banyuwangi - Dinda Mustika Putri; Moh. Halim; Arisita Nastiti (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aimed to analyze the process of applying for Murabahah financing and to analyze how the implementation of the Murabahah financing accounting system in Bank Syariah Mandiri KC Banyuwangi. This research method is descriptive qualitative. The data collection method used in this research is to use interviews, observation, and documentation. The results of this study indicate that Bank Syariah Mandiri KC Banyuwangi uses a binding method because the bank avoids the risk of damage and finds inventory. The current accounting system at BSM KC Banyuwangi has implemented a system related to forms, records and reports that have been coordinated and makes it easier for companies to manage all important data and forms and protect all data that has become confidential data for the company. In conclusion, Bank Syariah Mandiri KC Banyuwangi only applies one type of contract, namely the type of Murabahah contract which uses a binding order method, which means that the bank makes an offer as a seller if it wants an item. Keywords: Bank Syariah Mandiri KC Banyuwangi, Accounting System, Murabahah Financing